The Effect of Sex Variation on Hemato-Biochemical Profiles of Arabian Horses Raised in Libya - Fathia Benashour,; Fahima Alnagar,; Nadia Gregni,; Amal Buker,; Rabea Al zlitni,; Aboajeela Almashat, (AlQalam Journal of Medical and Applied Sciences, 2024)
As essential components of a minimal database, the hematological and biochemical blood profile are potent and significant diagnostic tools. Thus, the current study aimed to ascertain the serum biochemical and hematological characteristics, as well as any potential sex-related variations, of apparently healthy Arabian horses raised in Libya. The blood samples were collected from 65 clinically healthy horses of both sexes; males (n=26) and females (n=39) at winter season 2022 and included to analyze blood constituents and biochemical profile. The results of this study revealed that differences among Arabian horses according to gender factor not significant (p> 0.1) of all the parameters including the total white blood cells (WBC), red blood cells (RBC), hemoglobin (Hb), mean cellular volume (MCV), mean cellular hemoglobin (MCH), mean cellular hemoglobin concentration (MCHC), red cell width distribution-coefficient of variation (RDW-CV), red cell distribution width-standard deviation (RDW-SD), platelet count (PLT), mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT). Additionally, biochemical analysis showed no significant differences (p> 0.05) between stallions and mares of tested breed with exception of serum bilirubin, creatinine (Cr), urea, potassium (K) and chloride (Cl). This study shows no significant sex differences between male and female Arabian horses raised in Libya, whereas gender had only slight effect on the hematological and biochemical parameters. تعتبر الكيمياء الحيوية للدم وتعداد الدم الكامل أدوات تشخيصية قوية وهامة في مجال البحوث الطبية لما لها من قدرة على إعطاء صورة حقيقية (كمرآة) عن الوضع الفسيولوجي والأيضي للعينة المختبرة وأيضا باعتبارها مكونات أساسية لقاعدة بيانات بسيطة. لذلك كان الهدف من هذه الدراسة هو البحث في الخصائص البيوكيميائية والدموية في الدم ومدى تأثرها بعامل الجنس في الخيول العربية الأصيلة التي ولدت وترعرعت في ليبيا. تم جمع عينات الدم من 65 حصاناً سليماً سريرياً من كلا الجنسين؛ الذكور (العدد = 26) والإناث (العدد = 39) في فصل شتاء 2022 وضمنت للتحليل الدموي والكيميائي الحيوي. أظهرت نتائج هذه الدراسة أنه بين الخيول الذكور والإناث لا توجد فروق معنوية (P> 0.1) في جميع العوامل بما في ذلك إجمالي خلايا الدم البيضاء، خلايا الدم الحمراء، الهيموجلوبين، متوسط حجم الكريات، متوسط الهيموجلوبين الجسيمي، متوسط تركيز الهيموجلوبين داخل الكرية، معامل التباين لتوزيع عرض الخلية الحمراء، الانحراف المعياري لعرض توزيع الخلايا الحمراء، عدد الصفائح الدموية، متوسط حجم الصفائح الدموية، عرض توزيع الصفائح الدموية, والصفائح الدمويةالمضغوطة داخل حجم من البلازما. على مستوى الخصائص الكيموحيوية، أظهرت التحاليل عدم وجود فروق معنوية (P> 0.05) بين الذكور والإناث باستثناء مستويات البيليروبين في الدم والكرياتينين واليوريا والبوتاسيوم والكلوريد .أظهرت نتائج هذه الدراسة أن الجنس كان له تأثير طفيف على المعايير التي تم بحثها في الخيول العربية البالغة السليمة سريريا والتي نشأت في ليبيا مما قد يكون له عظيم الفائدة عند البحث في هذه السلالة.